Biofilm associated genotypes of multiple antibiotic resistant Pseudomonas aeruginosa - James Redfern; Janine Wallace; Alex van Belkum; Magali Jaillard; Elliot Whittard; Roobinidevi Ragupathy; Joanna Verran; Peter Kelly; Mark Charles Enright (BMC Genomics, 2021)
Abstract Background Pseudomonas aeruginosa is a ubiquitous environmental microorganism and also a common cause of infection. Its ability to survive in many different environments and persistently colonize humans is linked to its presence in biofilms formed on indwelling device surfaces. Biofilm promotes adhesion to, and survival on surfaces, protects from desiccation and the actions of antibiotics and disinfectants. Results We examined the genetic basis for biofilm production on polystyrene at room (22 °C) and body temperature (37 °C) within 280 P. aeruginosa. 193 isolates (69 %) produced more biofilm at 22 °C than at 37 °C. Using GWAS and pan-GWAS, we found a number of accessory genes significantly associated with greater biofilm production at 22 °C. Many of these are present on a 165 kb region containing genes for heavy metal resistance (arsenic, copper, mercury and cadmium), transcriptional regulators and methytransferases. We also discovered multiple core genome SNPs in the A-type flagellin gene and Type II secretion system gene xpsD. Analysis of biofilm production of isolates of the MDR ST111 and ST235 lineages on stainless-steel revealed several accessory genes associated with enhanced biofilm production. These include a putative translocase with homology to a Helicobacter pylori type IV secretion system protein, a TA system II toxin gene and the alginate biosynthesis gene algA, several transcriptional regulators and methytransferases as well as core SNPs in genes involved in quorum sensing and protein translocation. Conclusions Using genetic association approaches we discovered a number of accessory genes and core-genome SNPs that were associated with enhanced early biofilm formation at 22 °C compared to 37 °C. These included a 165 kb genomic island containing multiple heavy metal resistance genes, transcriptional regulators and methyltransferases. We hypothesize that this genomic island may be associated with overall genotypes that are environmentally adapted to survive at lower temperatures. Further work to examine their importance in, for example gene-knockout studies, are required to confirm their relevance. GWAS and pan-GWAS approaches have great potential as a first step in examining the genetic basis of novel bacterial phenotypes.